(untitled) (Tribhuvan University Journal of Food Science and Technology, 2023)
The use of herbs for preparing cereal-based alcoholic beverages probably dates back to ancient times. Although the database of such plants is still far from complete, literatures show that this practice prevails in South Asia, the Indian subcontinent, and the neighboring countries in particular. These plants (hereinafter called starter-plants) are used for the preparation of amylolytic starters, which in turn are used for the preparation of a range of traditional alcoholic beverages (both distilled and undistilled) and are also sold in the market as means of livelihood. Based on reports by different authors, the present review lists species of starter-plants from some 36 genera. The starter-plants serve as sources of essential microorganisms (yeasts, molds, and bacteria) for fermentation. However, except for articles written by few authors, work on isolation and identification of microbial flora from starter plants is virtually non-existent. Both starter plants and amylolytic starters have significant socio-economic contributions in the lives of ethnic people of South Asia. Some starter plants fetch very high price on selling and this has led to, at least in some places, their rapid dwindle. For instance, Polygala arillata has become commercially threatened and Inula sp. has become rare.